Fabrication of periodic nanoparticle arrays using nanosphere lithography technique and thin film gold as electrically enhanced catalysts - Md Juremi, Nor Rashidah (2012)
Nanosphere lithography (NSL) is a versatile, facile and parallel nanofabrication technique, especially in fabrication of periodic nanoparticle arrays (PNPAs) such as nanotriangles, nanohole arrays (PNHAs) and nanocups (NCs). In this research, single layer polystyrene nanospheres (PSNs) are chosen as templates thus be manipulated and modified using reactive ion etching (RIE). Ultrasonic agitation and sticking tape technique are used as lift-off process during fabrication of PNPAs. The morphology of PNPAs and confirmation element was characterized by field emission-scanning electron microscopy (FE-SEM) and energy dispersive x-ray spectroscopy (EDS or EDX) respectively. In this report, thin film gold supported by PSNs used as electrically enhanced catalysts for the chemical reaction of oxidation of styrene. The products were characterized by using gas chromatography (GC). Oxidation of styrene produced three main products which are benzaldehyde (B), phenylacetaldehyde (PA) and styrene oxide (SO). From the GC analysis, the catalyst which was given 3V positive bias voltage selectively increased the products. The products increased about 494.12%, 926.67% and 1162.10% for B, PA and SO, respectively.